The relationship between transformational leadership and succession planning among employees in public sector Perlis, Malaysia / Nur Hayziera Yusri - Yusri, Nur Hayziera
Although research about succession planning in family-business and private sector is growing rapidly, there is still no consensus regarding the implementation of succession planning in public sector. Thus, the purpose of this research is to study about the relationship between transformational leadership such as idealized influence, inspirational motivation, intellectual stimulation and individualized consideration on succession planning in public sector, Perlis. The researcher prepared 170 sets of questionnaires and distributed them to the targeted respondents who are currently working in the selected public sector in Perlis area. The researcher succeeded to collect data from 132 respondents. Researchers used SPSS version 21.0 to generate the data and provide the final result. The limitations for the study, significance of the study and recommendations for future research were also discussed.